Surveys assessing sports services and municipal governance - Júlia Bosch; Laureà Fanega; Jaume García Villar; Núria Hernández; Xavier Moya; Carlos Murillo (European Journal of Government and Economics (EJGE), 2020)
This study aims to investigate the social importance of sport in L'Hospitalet de Llobregat. As an instrument for social cohesion and integration, sport has become a very important part of municipal activity. We use two surveys: the Baròmetre, which gathers opinion about municipal services; and satisfaction surveys completed by the users of sports facilities. The sports offer (6.5) receives a better rating than overall municipal management (5.9), and counts for 20.4% of the global assessment of the municipal management. Satisfaction with facilities is 7.3 out of 10, while price receives the lowest mark. Detailed analysis of satisfaction surveys conducted among the population can help the municipal management of sports facilities. Policies that focus only on prices are unlikely to be as effective at improving members' perception of sports facilities as those that also take other aspects into account.
Keywords: C13; H41; H70; Z28; 330; local governance; satisfaction surveys; sports facilities; sports policy; sports services